The bioinorganic chemistry of chromium - Vincent, John B. (John Bertram) (Chichester, West Sussex : John Wiley & Sons, 2012)
"Chromium exists in nature as complexes of two stable oxidation states - trivalent chromium(III) and hexavalent chromium(VI). Although trivalent chromium is required in trace amounts for sugar and lipid metabolism in humans and its deficiency may cause a disease called chromium deficiency; hexavalent chromium is toxic and carcinogenic. As chromium compounds were used in dyes and paints and the tanning of leather, these compounds are often found in soil and groundwater at abandoned industrial sites, now needing environmental cleanup and remediation. The Bioinorganic Chemistry of Chromium: From Biochemistry to Environmental Toxicology takes a critical look at what the biochemical data indicate about chromium's role in the body and the biological mechanisms of its toxicology."--
Introduction the current status of chromium(III) -- Is chromium essential? : the evidence -- The story of glucose tolerance factor (GTF) -- Is chromium effective as a nutraceutical? -- Is chromium effective as a therapeutic agent? -- Biochemical mechanisms -- Menagerie of chromium supplements -- Potential use of chromium in the farm livestock industry -- Toxicology of chromium(III).
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Chromium; Chromium -- chemistry; Chromium -- therapeutic use; Chromium -- toxicity; MEDICAL -- Pharmacology; Chromium; Electronic books